Is the devil dressed in greed? Toward a peaceful, just, and sustainable world order - Roy I. Bhikharie (Cogent Social Sciences, 2024)
AbstractIs the devil dressed in greed? Greed stimulates corruption, which promotes self-alienation, facilitates systemic failure, worsens inequality, and generates false pledges and divide-and-conquer policies. Despite the United Nations’ (UN) existence for much of a century, most countries continue to exploit and compete for cheap labor, causing poverty rates to climb. Most UN member states and other affiliated and international organizations have institutionalized bad governance, corporate abuse, and social injustice to benefit themselves, thus committing institutional crimes and aiding the global elite in a vicious conspiratorial cycle. The entire UN system has harnessed a mafia-like culture of power with impunity in intermestic affairs to control human experience and generate authoritarian paradigms. This in turn stimulates psychological captivity, irrational preferences, and negative herd behavior and divides nations both internationally and domestically. A literature-based transdisciplinary study was conducted to substantiate these assertions and to propose feasible systemic solutions that point toward humanistic paradigms by cultivating psychological freedom and implementing good governance. In this way, the related cognitive processes can be systemically and intermestically amended while resolving the structural weaknesses of the UN, eliminating inequality, uniting nations internationally and domestically, and developing a peaceful, just, and sustainable world order.